Correlation of Body Mass Index, Physical Activity, and Physical Fitness in Elementary School Students - Ilmul Ma'arif; Nurhasan; Suroto; Risfandi Setyawan; Basuki; Mohammad Zaim Zen; Rahayu Prasetiyo; Yudi Dwi Saputra; Novita Nur Synthiawati (OVS LLC, 2023)
The purpose of this study was to determine the conditions and the relationship between body mass index (BMI), physical activity, and physical fitness. Materials and methods. This type of research was a cross-sectional study which was an observational study that analyzes data with predetermined variables and respondents. The number of respondents was 191 elementary school students in Kecamatan Ploso, Kabupaten Jombang, East Java, Indonesia. BMI was calculated by dividing weight in kilograms (kg) by height in meters squared (m2), measurement of physical fitness used 20-meter Multi-Stage Fitness Test (MSFT) test, whilst physical activity test used a Physical Activity Questionnaire for Older Children (PAQ-C). The data analysis used the Pearson product-moment model using SPSS version 21.0 with a significance level of 5%. Results. The correlation analysis results in this study indicate that there was a positive correlation between BMI and physical activity (r=0.176; p-value=0.015), BMI and physical fitness (r=0.151; p-value=0.037), and physical activity and physical fitness (r=0.142; p-value=0.049). Conclusions. Based on the study results, it was showed that there was a positive correlation in each variable (body mass index, physical activity, and physical fitness).